2011
DOI: 10.1021/es202534w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Perchlorate Formation on Boron-Doped Diamond Film Anodes

Abstract: This research investigated the mechanism of perchlorate (ClO(4)(-)) formation from chlorate (ClO(3)(-)) on boron-doped diamond (BDD) film anodes by use of a rotating disk electrode reactor. Rates of ClO(4)(-) formation were determined as functions of the electrode potential (2.29-2.70 V/standard hydrogen electrode, SHE) and temperature (10-40 °C). At all applied potentials and a ClO(3)(-) concentration of 1 mM, ClO(4)(-) production rates were zeroth-order with respect to ClO(4)(-) concentration. Experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 50 publications
5
121
0
Order By: Relevance
“…1). A decrease in the current efficiency can also be explained by the formation of oxidants that are weaker than Å OH radicals such as, Cl 2 or HClO/ClO À and which participate in the organic matter oxidation; moreover, these chlorine species can possibly be transformed into chlorine oxospecies [37]. The transformation can be correlated with the chloride disappearance and the possibility of creating perchlorate and chloroorganics in our system.…”
Section: The Influence Of Experimental Variables On Electrochemical Omentioning
confidence: 80%
“…1). A decrease in the current efficiency can also be explained by the formation of oxidants that are weaker than Å OH radicals such as, Cl 2 or HClO/ClO À and which participate in the organic matter oxidation; moreover, these chlorine species can possibly be transformed into chlorine oxospecies [37]. The transformation can be correlated with the chloride disappearance and the possibility of creating perchlorate and chloroorganics in our system.…”
Section: The Influence Of Experimental Variables On Electrochemical Omentioning
confidence: 80%
“…Recent research has shown that high concentrations of ClO 3 − and ClO 4 − are formed during electrolysis of Cl − solutions when BDD anodes are used [1][2][3][4][5][6][7][8][9]. The relationship between experimental conditions and chlorine speciation has been studied in those works and the most important parameters affecting ClO 3 − and ClO 4 − formation were found to be the mass-transfer rate and the concentration of competitive ions [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…HClO 4 [39] pharmaceuticals. This is the aim of proposing adequate operating conditions to limit the risk of formation of toxic by-products.…”
Section: CLmentioning
confidence: 99%
“…Since, for an electrical charge of 0. and OH [39]. The high concentration of electrogenerated oxygen species allows the reactions between the intermediate chlorine species and oxygen species to form ClO 4 À .…”
Section: It Is Evidenced That the Formation Of Clomentioning
confidence: 99%
See 1 more Smart Citation